Another Sky - Lambert, Gavin; Lassally, Walter; Lacey, Catherine; Forbes, Alan; Montague, Lee (Facets Video, 2007)
Rose, a demure and prim governess, arrives in Marrakesh to begin a new job as a paid companion to a wealthy English expatriate. As she explores the exotic environs of her new home, she is seduced by the men, music, and mystery of Morocco. The only film directed by screenwriter and film critic Gavin Lambert ("I Never Promised You a Rose Garden", "The Roman Spring of Mrs. Stone"), "Another Sky" was inspired by Lambert's peer and friend, Paul Bowles ("The Sheltering Sky"). The dreamy black and white cinematography by Walter Lassally captures the steamy atmosphere of North Africa in the 1950s, where a colony of expatriate artists and writers thrived in a bohemian existence. [Cover]